Blue 'turn-on' fluorescent probes for the direct detection of free radicals and nitric oxide in Pseudomonas aeruginosa biofilms. Issue 7 (21st January 2016) - Barzegar Amiri Olia, Mina; Zavras, Athanasios; Schiesser, Carl H.; Alexander, Stefanie-Ann
Abstract : Novel blue cell-permeable 'turn-on' fluorescent probes have been developed to visualize and quantify nitric oxide and free radical formation and reaction within a Pseudomonas aeruginosa biofilm. Abstract : Two novel cell-permeable and bacteria-compatible 'turn-on' fluorescent probes, designed to be compatible in a multi-dye system and to fluoresce in the blue region exhibiting emission maxima of 440–490 nm, were synthesized. The profluorescent nitroxide probe (11 ) was developed to visualize and quantify free radical and redox processes, and the Cu(ii )-complexed coumarin-based probe (16a ) was developed for NO detection. Confocal laser-scanning microscopy and subsequent digital analysis of Pseudomonas aeruginosa biofilms stained with11 or16a determined that free radical and redox processes and NO generation occur predominantly in live cells during normal biofilm growth.